APPLICATION OF SYMMETRIC AND ASYMMETRIC-KEY CRYPTOGRAPHY FOR SECURING MULTIMEDIA MESSAGING SERVICE (MMS) - Halim - NIM : 13501060, Abdul
Abstract: Messaging technology in mobile telecommunication services has evolved from just a simple text-based messaging service to message that can contains graphics, voices or videos. This technology, Multimedia Messaging Service (MMS), currently is a standard service given by cellular operators. However various security threats can occur such as theft so that thief can read all the messages in cellphone, messagetapping, et cetera. In this final project, a software is developed to secure MMS messages using symmetric and asymmetric-key cryptography. It uses Rivest, Shamir and Adleman (RSA) algorithm for asymmetric-key and Advanced Encryption Standard (AES) algorithm for symmetric-key. The software is implemented by building main software in two entities, a software installed in cell phones and a web-based software. Main software functions are securing MMS using encryption, generating digital signature. Meanwhile, web-based application is for transferring public key among users which can be accessed through main software. Main software was developed for cellular telephone using Symbian operating system version 70 or 80 series 60 and Software Development Kit (SDK) from Nokia also Microsoft Visual Studio .NET123 2003 with C++ programming language. According to the test, the software is able to process encryption, decryption, digital signature signing and verification at MMS, but is not able to send encrypted MMS so it is open to further development. At the end of this final project, it can be concluded that symmetric and asymmetric-key cryptography is one of the suitable solution and can be applied for securing MMS in cell phones.